Ternary vanadium-titanium-niobium lithium ion sieve based on biomimetic mineralization template as well as lithium extraction device and lithium extraction process of ternary vanadium-titanium-niobium lithium ion sieve
By using biomimetic mineralization templates and ternary metals for synergistic modification, a multi-level pore structure and gradient lattice stabilized lithium-ion sieve were constructed, solving the problems of low adsorption capacity, poor selectivity and short cycle life of traditional titanium-based lithium-ion sieves in lithium extraction from salt lakes, thus realizing efficient and low-cost development of salt lake lithium resources.
Patent Information
- Application Number
- CN202511527924.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-24
- Publication Date
- 2026-01-02
AI Technical Summary
Existing titanium-based lithium-ion sieves suffer from problems such as low adsorption capacity, poor magnesium-lithium selectivity, short cycle life, and insufficient process adaptability in the process of lithium extraction from salt lakes. In particular, they are difficult to meet industrial requirements in salt lake brines with high magnesium-lithium ratios and high chloride ion concentrations.
A biomimetic mineralization template and ternary metal synergistic modification method were adopted to prepare Li1.2H0.8Ti(1-xy)VxNbyO4-δ lithium-ion sieve through multi-scale pore structure design, oxygen vacancy directional control and gradient lattice stabilization technology. The material properties and process parameters were optimized by combining gradient desorption process and membrane coupling technology.
It achieves high mass transfer efficiency, excellent magnesium-lithium selectivity and long cycle stability, improves adsorption capacity and selectivity, reduces acid consumption and energy consumption, improves lithium recovery rate and equipment life, and meets industrial needs.
Abstract
Description
TECHNICAL FIELD
[0001] The application belongs to the technical field of high-performance adsorption materials for lithium extraction from salt lake brine, and relates to a ternary vanadium-titanium-niobium lithium ion sieve based on a biomimetic mineralization template, as well as a lithium extraction device and a lithium extraction process. BACKGROUND
[0002] Lithium, as a "green energy metal" in the 21st century, has seen exponential growth in demand due to its application in power batteries, energy storage devices, and other fields. Salt lake brine, as the main form of global lithium resources, has become the core focus of resource strategies in various countries. China is rich in salt lake lithium resources, but generally presents complex characteristics such as high magnesium-lithium ratio, high salinity, and coexistence of multiple ions. Traditional lithium extraction technologies such as precipitation and extraction have low separation efficiency due to the similar water radius and chemical properties of magnesium and lithium ions, and are accompanied by high energy consumption and strong pollution.
[0003] Adsorption is considered a revolutionary direction for lithium extraction from salt lakes due to its high selectivity and flexible operation. Titanium-based lithium ion sieves have attracted attention due to their high theoretical adsorption capacity and resistance to strong acids and bases. However, the industrial application of existing titanium-based sieves still faces multiple technical bottlenecks: first, traditional synthesis processes rely on a single template to construct mesoporous structures, with a specific surface area generally lower than 50 m 2 / g, and the pore system is mostly isolated or low-connectivity, resulting in high mass transfer resistance and slow dynamic adsorption rate, making it difficult to match the high flow rate requirements of industrial adsorption columns; second, the selectivity of titanium-based materials for magnesium and lithium ions mainly relies on ion sieving effects, but conventional modification methods such as single-metal doping easily damage the integrity of the crystal structure, leading to a decrease in active site density, and in practical applications, there is often a "high selectivity-low capacity" dilemma, with typical titanium-based sieves having a magnesium-lithium selectivity ratio of less than 120:1 in Mg 2+ / Li⁺=50:1 brine, and a corresponding adsorption capacity of only 12-15 mg / g; third, the acid desorption process easily causes lattice collapse and loss of active sites, resulting in poor cycle stability, research shows that the adsorption capacity of traditional titanium sieves decreases by more than 40% after 30 cycles, and the lithium recovery rate of the desorption solution is less than 80%, while producing high-acidity wastewater with pH<1.5; fourth, in existing adsorption-membrane coupling processes, the acid residue and colloidal particles with pH<3 in the adsorption tail liquid easily cause membrane pollution, resulting in a 30%-50% decrease in membrane flux, the overall recovery rate of the system is less than 75%, and the energy consumption is as high as 6-8 kWh / m 3 .
[0004] To break through the above bottleneck, the industry tries to improve by multi-doping, composite pore design and process optimization, but there are still significant limitations: double metal doping such as Fe-Ti-O system can improve part of the selectivity, but the adsorption capacity is limited, generally <25 mg / g; multi-stage pore construction technology can increase the specific surface area, but the lack of micropores leads to insufficient ion sieving efficiency; low-temperature desorption process such as CO2 acidification can reduce acid consumption, but the desorption efficiency is less than 80%, and the equipment complexity increases dramatically. In addition, the existing technology focuses on single performance optimization, and lacks the coordinated design of materials and processes, making it difficult to balance the adsorption kinetics, selectivity and cycle life in the industrial system, especially in the actual salt lake brine system with high magnesium-lithium ratio >50:1 and high chloride ion concentration >200 g / L. The comprehensive performance of the existing titanium sieve is still far from the industrial requirements of adsorption capacity >30 mg / g, selectivity ratio >200:1, and cycle life >50 times. Therefore, developing a new type of titanium lithium ion sieve with high mass transfer efficiency, excellent magnesium-lithium selectivity and long cycle stability, and its adaptive process system, has become an urgent need to promote the upgrading of salt lake lithium extraction technology and ensure the sustainable supply of lithium resources. SUMMARY
[0005] The present application aims to solve the technical defects of low adsorption capacity, poor magnesium-lithium selectivity, short cycle life and insufficient process adaptability of existing titanium lithium ion sieves. A titanium lithium ion sieve based on biomimetic mineralization template and ternary metal cooperative modification and its preparation method are proposed. Through the synergistic effect of multi-scale pore structure design, directional regulation of oxygen vacancies and gradient lattice stabilization technology, the material adsorption kinetics, selectivity and stability are broken through in all directions. At the same time, the preparation process of the material and its integrated application scheme in the dynamic adsorption-desorption system are covered, providing an innovative technical path to solve the industry problems of low adsorption capacity, poor selectivity and insufficient regeneration performance of traditional titanium lithium sieves.
[0006] To achieve the above purpose, the core innovation points and technical solutions of the present application are as follows: the chemical formula of a lithium ion sieve is Li 1.2 H 0.8 Ti (1-x-y) V x Nb y O4-δ, wherein the vanadium doping amount x is in the range of 0.05≤x≤0.15, the niobium doping amount y is in the range of 0.02≤y≤0.08, and the oxygen vacancy concentration δ is in the range of 0.2≤δ≤0.5.
[0007] Further, the preparation method of the lithium ion sieve comprises the following steps:
[0008] (1) Diatomite as a biological template, etched by 8-12% hydrofluoric acid solution for 20-40 min, then activated by 0.5-1.5 mol / L ammonia solution at 60 ℃ for 3 hours, to obtain a template skeleton with three-level through-pore channels;
[0009] (2) Tetrabutyl titanate, ammonium metavanadate and niobium oxalate were mixed according to the molar ratio of Ti:V:Nb=1:(0.05-0.15):(0.02-0.08), and citric acid complexing agent was added, and a vanadium-titanium-niobium ternary co-doped sol was synthesized under the conditions of microwave frequency 2.45 GHz and power 400-600 W;
[0010] (3) The template was immersed in the sol, and the sol was completely filled into the pores by vacuum negative pressure infiltration treatment, and then gradient calcination was carried out: the first stage was to heat to 400 ℃ at 2-5 ℃ / min under nitrogen atmosphere and keep for 2 hours to form mesoporous skeleton, the second stage was to heat to 600 ℃ at 5 ℃ / min in H2 / Ar (5:95) mixed gas and keep for 1 hour to generate oxygen vacancies, and the third stage was to cool to 550 ℃ in air and keep for 3 hours to stabilize the lattice structure;
[0011] (4) The calcined product was crushed and sieved to 80-200 mesh to obtain a lithium ion sieve with anatase-brookite mixed crystal structure.
[0012] Further, the multi-level pore system of the lithium ion sieve comprises: 50-200 nm macropores formed by replicating the original pores of diatomite templates; 5-20 nm mesopores constructed by interfacial self-assembly of CTAB template agent and sol; and 0.5-2 nm micropores spontaneously generated by lattice distortion caused by vanadium doping, the volume proportions of the three-level pores are 40-55%, 25-35%, and 15-25% respectively, the specific surface area of the material is 180-250 m 2 / g, and the total pore volume is 0.65-0.85 cm 3 / g.
[0013] Further, in the gradient calcination process, the vanadium doping amount x and the first stage calcination temperature T1 satisfy the function relationship x=0.0013(T1-385)²+0.048 (380 ℃≤T1≤420 ℃), the niobium doping amount y and the second stage calcination temperature T2 satisfy y=0.00075(T2-585)²+0.019 (580 ℃≤T2≤620 ℃), and the oxygen vacancy concentration δ and the third stage calcination time t satisfy δ=0.015(t-2.7)²+0.253 (2.0 h≤t≤4.0 h).
[0014] Further, the surface Zeta potential of the lithium ion sieve is -32.5 mV at pH=6.5, the oxygen vacancy concentration is 1.2×1021 / cm 3 The lithium ion diffusion activation energy is 28.5 kJ / mol.
[0015] Further, the application method of the lithium ion sieve in a dynamic adsorption column comprises the following steps: after the pH of the brine is adjusted to 6.5-7.5, the brine is passed through the adsorption column filled with the ion sieve at a flow rate of 1.5-2.5 BV / h, after adsorption saturation, CO2 gas and 0.3-0.7 mol / L hydrochloric acid are introduced in stages at a flow rate of 0.5-1.5 L / min, and the desorption liquid is concentrated through a nanofiltration membrane with a molecular weight cut-off of 300 Da, so that the lithium ion purity is greater than or equal to 99.3%.
[0016] Further, the regeneration method of the adsorption column comprises the following steps: mechanical impurities are removed by reverse pulse water flow flushing at a flow rate of 3-5 BV / h for 15 min, a regeneration liquid containing 0.05-0.15 mol / L LiOH and 0.02-0.05 mol / L EDTA is pumped at a temperature of 50-65 DEG C for 1-2 hours, and finally hot air drying is performed at 40-60 DEG C under nitrogen protection until the water content is less than 3%.
[0017] Further, the lithium ion sieve is used in Mg 2+ The saturated adsorption capacity of the lithium ion sieve in simulated brine with a concentration of 5 g / L and a pH of 6.5 is 42.7 mg / g, the adsorption capacity reaches 95% of the equilibrium capacity in 30 minutes, the capacity retention rate is greater than or equal to 91.3% after 50 cycles, and the lithium recovery rate of the desorption liquid is greater than or equal to 95%.
[0018] Further, in the membrane coupling system matched with the lithium ion sieve, the adsorption tail liquid is introduced into a nanofiltration unit after the pH is adjusted back to 4.0-4.5, the membrane flux is maintained at 18-22 L / (m 2 ·h), the comprehensive lithium recovery rate of the system is greater than or equal to 92%, and the energy consumption is less than or equal to 4.5 kWh / m 3 .
[0019] Further, in the preparation method, four groups of symmetrical waveguide antennas are arranged in the microwave reaction cavity, the power fluctuation is less than or equal to ±5%, the sol Zeta potential is controlled to be-25 mV to-35 mV, and the viscosity is 120-180 mPa·s.
[0020] Further, the crystal phase structure of the lithium ion sieve determines that the ratio of anatase to brookite is 6:4, the bond length difference of [TiO6]-[VO4] at the mixed crystal interface is 0.08 Å, and the channel tortuosity τ is 1.8-2.2.
[0021] The beneficial effects of the present application are:
[0022] 1. By synergistic modification of biomimetic templates and ternary metals, a composite structure with multi-level channels and oxygen vacancy regulation is constructed, which breaks through the limitations of traditional titanium-based materials with single channels and insufficient active sites. The optimal balance between adsorption capacity, selectivity and mass transfer efficiency is achieved, providing a high-performance material basis for lithium extraction from high magnesium-to-lithium ratio brines and promoting the industrialization of adsorption methods.
[0023] 2. Innovative gradient desorption process and membrane coupling technology, through precise matching of material properties and process parameters, significantly reduce acid consumption, energy consumption and wastewater treatment costs, solve the pain points of low efficiency and heavy pollution of traditional processes, and form a green and efficient systematic solution for lithium extraction from salt lakes.
[0024] 3. Based on lattice stabilization design and intelligent regeneration strategy, the material maintains long-term cycle performance in complex brine environments, breaking through the technical bottleneck of frequent adsorbent replacement, significantly extending the service life of equipment, and providing technical support for the large-scale and sustainable development of salt lake lithium resources. Detailed Implementation
[0025] The technical solutions of the present invention are described in detail below with reference to embodiments, but the scope of protection of the present invention is not limited to the following embodiments. To better understand the above technical solutions, the technical solutions of the embodiments of this application are described in detail below with reference to specific embodiments. It should be understood that the embodiments of this application and the specific features in the embodiments are detailed descriptions of the technical solutions of the embodiments of this application, and not limitations on the technical solutions of this application. Unless otherwise specified, the embodiments of this application and the technical features in the embodiments can be combined with each other.
[0026] Example 1
[0027] 1) Biological template pretreatment
[0028] 200 g of diatomaceous earth with a SiO2 content ≥96% and a native pore size of 90-150 μm was immersed in a 10% hydrofluoric acid solution and ultrasonically treated at 40 kHz and 300 W for 40 min to remove impurities and expand pores. After acid treatment, it was washed with deionized water until neutral, and then immersed in a 1.2 mol / L ammonia solution with a liquid-to-solid ratio of 15:1. The solution was then kept at 65 ℃ and shaken for 4 hours, followed by centrifugation and drying to obtain a specific surface area of 220 m². 2 / g, pore volume 0.78 cm³ 3 / g porous template.
[0029] 2) Synthesis of ternary precursor sol
[0030] Weigh out 72.4 g of tetrabutyl titanate, 5.1 g of ammonium metavanadate, and 3.7 g of niobium oxalate according to the molar ratio of Ti:V:Nb=1:0.12:0.06; add citric acid (metal ion:citric acid=1:3) as a complexing agent according to the molar ratio, and dissolve it in 600 mL of ethanol-water mixture with a volume ratio of 4:1; place it in a microwave reactor with a frequency of 2.42 GHz and a power of 550 W and irradiate for 40 minutes to form a uniform ternary precursor sol with a viscosity of 165 mPa·s and a Zeta potential of -28 mV.
[0031] 3) Template load
[0032] The porous biotemplate obtained in step 1) is immersed in the ternary precursor sol obtained in step 2), and the immersion is carried out three times under a vacuum of -0.1 MPa, each time for 15 minutes, to ensure that the ternary precursor sol fully fills the pores of the biotemplate.
[0033] 4) Gradient calcination process:
[0034] a) First stage: Nitrogen pre-crystallization, heating to 410℃ at 4℃ / min under nitrogen atmosphere, nitrogen flow rate maintained at 250 mL / min, holding for 2.5 hours to form anatase mesoporous framework;
[0035] b) Second stage: Hydrogen reduction, switch to a mixed gas with H2 / Ar volume ratio of 6:92, heat to 610℃ at 6 ℃ / min, and hold for 1.2 hours;
[0036] c) Third stage: air stabilization, cooling to 550℃ in air at 2℃ / min, holding for 3.5 hours to obtain dark gray powder.
[0037] d) Post-processing: The calcined product is crushed to 100-150 mesh by a jaw crusher to obtain a ternary doped titanium-based lithium ion sieve, which is stored in a dry nitrogen atmosphere.
[0038] 5) Calculation using the general formula
[0039] Vanadium doping concentration x = 0.12, niobium doping concentration y = 0.06
[0040] According to the formula in claim 1, the oxygen vacancy concentration δ can be calculated using the third-stage calcination time t = 3.5 h:
[0041] δ=0.015(3.5−2.7) 2 +0.253 = 0.015 × 0.64 + 0.253 ≈ 0.2626 Let δ ≈ 0.26
[0042] The lithium-ion sieve formula is: Li 1.2 H 0.8 Ti0.82 V 0.12 Nb 0.06 O 3.74
[0043] 6) Material characterization and performance testing
[0044] a) Saturated adsorption capacity determination: Accurately weigh 0.100 g of the dried ion sieve material obtained in step 4), and place it in 100 mL of 0.12 g / L Li₂ solution. + In the solution, Mg 2+ The concentration is 6 g / L, Li + The concentration was 0.12 g / L, pH buffered to 6.6, and the solution was shaken at 150 rpm for 24 hours at 25°C until adsorption equilibrium was reached. The supernatant was filtered, and the residual Li in the solution was determined by atomic absorption spectrometry. + Based on the concentration, the saturated adsorption capacity was calculated to be 44.2 mg / g, and the adsorption capacity reached 96% of the equilibrium capacity in 35 minutes.
[0045] b) Adsorption kinetics test: The method is the same as above. Samples are taken at different time intervals, such as 5, 10, 15, 20, 30, 45, 60, 90, and 120 min, to measure the Li content in the solution. + The concentration was calculated, and the adsorption amount at different time points was determined. It was found that the adsorption amount reached 96% of the equilibrium capacity after 35 minutes.
[0046] c) Magnesium-Lithium Selectivity: (This refers to the preparation of Mg...) 2+ / Li + An initial concentration ratio of 50:1 was used to prepare a mixed solution with pH 6.6. 0.1000 g of the material was used for adsorption equilibrium experiments, following the same method as for determining the saturated adsorption capacity. The Li content in the solution was measured before and after adsorption. + and Mg 2+ The concentration of magnesium and lithium was used to calculate the partition coefficient, and the magnesium-lithium selectivity ratio was found to be 372:1.
[0047] d) Cyclic Stability: Weigh 0.1000 g of material and conduct an adsorption-desorption cycle experiment. Adsorption conditions are the same as above. After adsorption saturation, filter the material and use 50 mL of 0.5 mol / L HCl solution as the desorption solution, desorbing at 25°C for 2 hours. After desorption, wash the material with deionized water until neutral and dry at 80°C, which constitutes one cycle. Repeat this process 50 times, and measure the saturated adsorption capacity after every 10 cycles. Calculate the ratio of the adsorption capacity after the 50th cycle to the initial adsorption capacity, obtaining a capacity retention rate of 92.5%.
[0048] Example 2
[0049] To investigate the regulatory effect of the second-stage calcination temperature on oxygen vacancy concentration and adsorption capacity.
[0050] 1) Group design: Three groups of materials were prepared according to the method in Example 1, with only the calcination temperature of the second stage adjusted, as follows; the remaining experimental steps were the same as in Example 1:
[0051] Group A: 590 ℃; Group B: 610 ℃ (Baseline of Example 1); Group C: 630 ℃.
[0052] 2) General Calculation: Only the calcination temperature of the second stage was adjusted in each group; the V and Nb doping ratios remained the same as in Example 1, i.e.:
[0053] x=0.12 y=0.06
[0054] The value of δ varies with calcination temperature, but the general formula remains unchanged: Li 1.2 H 0.8 Ti 0.82 V 0.12 Nb 0.06 O 4-δ
[0055] in:
[0056] Group A (590℃): δ≈ 0.21 General formula: Li 1.2 H 0.8 Ti 0.82 V 0.12 Nb 0.06 O 3.79
[0057] Group B (610℃): δ ≈ 0.26 General formula: Li 1.2 H 0.8 Ti 0.82 V 0.12 Nb 0.06 O 3.74 (Same as Example 1)
[0058] Group C (630℃): δ ≈ 0.35 General formula: Li 1.2 H 0.8 Ti 0.82 V 0.12 Nb 0.06 O 3.65
[0059] 3) Performance Comparison:
[0060] Oxygen vacancy concentration: Group A: 1.05 × 10⁻⁶ 21 / cm 3 Group B: 1.25 × 10 21 / cm 3Group C: 1.48 × 10 21 / cm 3 .
[0061] Magnesium-lithium selectivity ratio: Group A: 335:1; Group B: 372:1; Group C: 318:1.
[0062] 4) Adsorption capacity: Group A: 39.8 mg / g (insufficient oxygen vacancies, fewer active sites); Group B: 44.2 mg / g (optimal equilibrium); Group C: 37.6 mg / g (high temperature caused mesoporous collapse, specific surface area decreased to 185 m²). 2 / g).
[0063] 5) Cyclic stability: After 50 cycles, the capacity retention rate of group A was 88.2%; that of group B was 92.3%; and that of group C decreased to 79.5%.
[0064] 6) Structural stability:
[0065] a) Group A had insufficient reduction temperature, a fully developed mesoporous framework but low oxygen vacancy concentration, a mesoporous wall thickness of about 22 nm, good pore connectivity but insufficient active site density.
[0066] b) Group B has a suitable reduction temperature, which allows for the formation of high concentrations of oxygen vacancies while maintaining a good mesoporous structure with a stable wall thickness of 24-26 nm, optimal pore connectivity, and high structural stability.
[0067] c) The mesopore wall thickness of group C increased to 35 nm, compared to the original 25 nm. Some mesopores collapsed or closed, resulting in reduced pore connectivity and a decrease in specific surface area.
[0068] Conclusion: 610 ℃ is the optimal calcination temperature, which balances oxygen vacancy concentration and structural stability.
[0069] Example 3
[0070] To determine the synergistic effect of vanadium and niobium doping ratio on material properties.
[0071] 1) Group design: Three groups of materials were prepared by fixing the Ti content and adjusting the V / Nb ratio.
[0072] Group D: Ti:V:Nb=1:0.08:0.04 (low doping); Group E: Ti:V:Nb=1:0.12:0.06 (Based on Example 1);
[0073] Group F: Ti:V:Nb=1:0.18:0.09 (highly doped), the remaining steps are the same as in Example 1.
[0074] 2) General formula calculation
[0075] The three groups of materials, D, E, and F, had their vanadium and niobium doping ratios specifically adjusted.
[0076] Group D (Low Doping): Ti:V:Nb = 1: 0.08: 0.04 x = 0.08 y = 0.04
[0077] General formula: Li 1.2 H 0.8 Ti 0.88 V 0.08 Nb 0.04 O
[0078] Group E (Baseline): Ti:V:Nb = 1: 0.12: 0.06 x = 0.12 y = 0.06 (Same as Example 1)
[0079] General formula: Li1.2H0.8Ti0. 82 V0. 12 Nb0. 06 O3. 74
[0080] Group F (highly doped): Ti:V:Nb = 1: 0.18: 0.09 x = 0.18, y = 0.09
[0081] General formula: Li 1.2 H 0.8 Ti 0.73 V 0.18 Nb 0.09 O 3.74
[0082] 3) Performance Comparison
[0083] a) Adsorption capacity: Group D: 38.3 mg / g; Group E: 44.1 mg / g; Group F: 41.2 mg / g.
[0084] b) Magnesium-lithium selectivity ratio: Group D: 328:1; Group E: 372:1; Group F: 345:1.
[0085] c) Cyclic stability: Group D had a capacity retention of 89.5% after 50 cycles; Group E had a capacity retention of 92.3% after 50 cycles; and Group F had a capacity retention that decreased to 86% after 50 cycles.
[0086] Conclusion: The optimal ratio of Ti:V:Nb is 1:0.12:0.06, which combines the advantages of large adsorption capacity, selectivity and stability.
[0087] Example 4
[0088] Verify the comprehensive effectiveness of the materials and processes of this invention in large-scale production.
[0089] 1) System Configuration
[0090] a) Pretreatment unit: pH adjustment module with an accuracy range of ±0.05, maintaining brine pH at 6.4-6.9; temperature control unit with temperature controlled at 23-28℃.
[0091] b) Adsorption column unit: A 316 L stainless steel column with a diameter of 40 cm and a height of 4.8 m is used, filled with the ternary doped titanium-based lithium ion sieve material prepared in Example 1, with a filling height of 4.0 m and a bed height-to-diameter ratio of 12:1;
[0092] c) Desorption and regeneration unit: This includes a CO2 gas injection unit and a hydrochloric acid gradient elution device. CO2 gas is introduced from the bottom of the adsorption column at a flow rate of 1.2 L / min for pretreatment for 35 minutes, followed by elution with 0.5 mol / L HCl pumped in at a flow rate of 0.8 BV / h.
[0093] d) Membrane separation unit: Employs an acid-resistant nanofiltration membrane with a molecular weight cutoff of 350 Da and a membrane area of 10 m². 2 The operating pressure during this process is maintained at 2.8 ± 0.2 MPa.
[0094] 2) Operating parameters
[0095] a) Raw brine: Li⁺ concentration is 0.09 g / L, Mg 2+ The brine from a salt lake in Tibet has a concentration of 5.2 g / L, a Cl⁻ concentration of 240 g / L, a pH of 6.8, and a temperature of 25℃.
[0096] b) Adsorption stage: The brine flows from top to bottom through the adsorption column at a flow rate of 2.1 BV / h. The adsorption column is loaded with a ternary doped titanium-based lithium-ion sieve prepared in Example 1. The bed pressure drop monitoring value is 0.13 MPa / m.
[0097] c) Desorption stage: After adsorption saturation, the feed is stopped. 99.5% pure CO2 gas is introduced from the bottom of the adsorption column at a flow rate of 1.2 L / min, contacting the adsorbent bed for 35 minutes, achieving a desorption rate of 70%. This process aims to initially release some of the adsorbed lithium ions through a weakly acidic environment and reduce acid consumption for subsequent strong acid desorption. During the pretreatment stage, the column top vent valve is kept slightly open to maintain a system pressure <0.1 MPa. After CO2 pretreatment, 0.5 mol / L hydrochloric acid solution is pumped in at a flow rate of 0.8 BV / h for elution. The eluent is collected until the lithium concentration in the effluent is below 50 mg / L, achieving a total desorption rate of 98.8%.
[0098] d) Membrane concentration stage: After the desorbate is adjusted to pH 4.5 with NaOH solution, the membrane flux is 22 L / (m²). 2 ·h), the concentrated Li⁺ solution has a purity of 99.5%.
[0099] 3) Execution Results
[0100] a) Lithium recovery rate: 94.1%, compared to ≤76% for traditional processes;
[0101] b) Acid consumption: 1.6 tons of HCl and 1.9 tons of Li2CO3, compared to 3.5 tons for the traditional process;
[0102] c) Energy consumption: 4.1 kWh / m 3 Traditional system 8.5 kWh / m 3 ;
[0103] Comparative Example: Performance Comparison of Traditional Lithium Titanate Screens
[0104] 1) Raw materials and processes
[0105] a) Precursor: Only tetrabutyl titanate is used, without vanadium or niobium doping;
[0106] b) Template treatment: Diatomaceous earth bio-templates were not used; instead, 20% by mass of P123 surfactant was used directly as a mesoporous template.
[0107] c) Sol synthesis: Tetrabutyl titanate and citric acid in a molar ratio of 1:2 are dissolved in an ethanol-water mixture in a volume ratio of 1:1 and stirred at room temperature for 24 hours.
[0108] d) Calcination process: The temperature was increased to 600℃ at 2℃ / min under a single air atmosphere and held for 3 hours without gradient reduction treatment.
[0109] e) Material forming: Crush and screen to 100-150 mesh to obtain performance data of pure lithium titanate ion screen.
[0110] Performance Comparison Analysis
[0111] 1) Structural characteristics
[0112] a) Specific surface area: approximately 41 m² 2 / g, only the material in Example 1, 225 m 2 / g 18.7%;
[0113] b) Pore system: Single mesoporous structure, pore size approximately 5-8 nm, no macropores, micropore volume ratio <5%;
[0114] c) Crystal phase composition: single anatase phase, no mixed crystal structure, compared with the anatase-brookite 6.5:3.5 of Example 1.
[0115] 2) Adsorption performance
[0116] a) Saturated adsorption capacity: 13.7 mg / g, compared to 44.2 mg / g in Example 1, which is only 31.2% of the material of this invention;
[0117] b) Magnesium-lithium selectivity ratio: 112:1, compared to 372:1 in Example 1, indicating a significant decrease in lithium-ion selectivity;
[0118] c) Adsorption kinetics: Equilibrium time > 2 hours, 35 minutes in Example 1, resulting in low mass transfer efficiency.
[0119] 3) Cyclic stability
[0120] a) Capacity decay: After 50 cycles, the adsorption capacity retention rate was 54%, compared to 92.3% in Example 1;
[0121] b) Desorption efficiency: 2 mol / L hydrochloric acid is required for desorption, and the lithium recovery rate of the desorbed solution is only 78%, compared to 98.8% in Example 1.
[0122] 4) Industrial adaptability:
[0123] a) Dynamic column performance: When the flow rate is >1.5 BV / h, the pressure drop exceeds 0.3 MPa / m, which cannot meet the high flow rate requirements;
[0124] b) Membrane fouling issue: The adsorption tail liquid had a pH of 2.8, which, when directly introduced into the nanofiltration system, caused a 52% decrease in membrane flux. In Example 1, the flux was maintained at 22 L / (m³) by adjusting the pH back to 4.5. 2 ·h);
[0125] c) Overall recovery rate: Lithium recovery rate ≤ 68%, energy consumption as high as 8.5 kWh / m³ 3 Example 1 has a concentration of 4.1 kWh / m³. 3 .
[0126] The implementation of this invention verifies its significant technological breakthrough and industrial application potential in the field of lithium extraction from salt lakes. By integrating a biomimetic mineralization template-guided three-level channel design, synergistic modification of vanadium-titanium-niobium ternary metal-oxygen clusters, and gradient lattice control technology, the core challenges of low adsorption capacity and the difficulty in simultaneously achieving magnesium-lithium selectivity and cycle stability in traditional titanium-based lithium-ion sieves are successfully solved. Experimental data show that the material exhibits a saturated adsorption capacity of 42.4 mg / g and a magnesium-lithium selectivity ratio of 356:1 in simulated high magnesium-lithium ratio brine, representing a 2-3 times performance improvement over traditional titanium sieves, and the capacity retention rate remains stable at over 92% after 50 cycles. Data from the industrial pilot system operation shows that the overall lithium recovery rate exceeds 94%, acid consumption is reduced to 1.7 tons of HCl / ton of Li₂CO₃, and energy consumption is only 4.1 kWh / m³.3 This technology reduces costs by more than 40% compared to existing processes, providing an economical and efficient technological path for the large-scale development of lithium resources in salt lakes.
[0127] The scope of protection of this invention is defined by the claims, but is not limited to the embodiments described. Any equivalent substitutions or parameter adjustments based on the core principles of this invention, such as using different biological templates, adjusting the calcination atmosphere ratio, or optimizing the membrane separation unit configuration, fall within the scope of protection of this patent. In the future, by combining with IoT technology, a real-time monitoring system for the adsorption column's operating status can be developed, or machine learning algorithms can be introduced to optimize desorption gradient control, further improving the level of process intelligence.
[0128] In summary, this invention, based on material innovation, has constructed a complete technical system from microstructure design to macro process integration. Its industrialization and promotion will strongly promote the technological upgrading of the global salt lake lithium extraction industry and provide a solid guarantee for the safe supply and sustainable development of lithium resources in the new energy era.
Claims
1. A ternary doped titanium-based lithium-ion sieve based on a biological template, characterized in that, Its chemical composition satisfies the general formula: Li 1.2 H 0.8 Ti (1-x-y) V x Nb y O4-δ, where The vanadium doping amount x is in the range of 0.05 ≤ x ≤ 0.15, and satisfies x = 0.0013(T1-385). 2 +0.048, T1 is the temperature of the first calcination stage (380℃≤T1≤420℃). The niobium doping amount y is in the range of 0.02≤y≤0.08, and satisfies y=0.00075(T2-585). 2 +0.019, T2 is the temperature of the second calcination stage (580℃≤T2≤620℃). The oxygen vacancy concentration δ is in the range of 0.2 ≤ δ ≤ 0.5, and satisfies δ = 0.015(t - 2.7). 2 +0.253, where t is the time of the third calcination stage (2.0 h ≤ t ≤ 10.0 h).
2. The method for preparing a ternary doped titanium-based lithium-ion sieve based on a biological template as described in claim 1, characterized in that, Includes the following steps: a) Pretreatment of biological template: Diatomaceous earth was immersed in a hydrofluoric acid solution with a mass concentration of 10±2% and ultrasonically treated. Then, it was activated by constant temperature shaking at 58-65℃ for 2.5-4 hours with a 1.0±0.4 mol / L ammonia solution to obtain a biological template with interconnected channels. b) Synthesis of ternary precursor sol: Tetrabutyl titanate, ammonium metavanadate, and niobium oxalate were mixed in a molar ratio of Ti:V:Nb=1:0.08-0.18:0.04-0.09, citric acid was added, and the mixture was irradiated in a microwave reactor at a frequency of 2.42 GHz and a power of 550±50 W for 35-40 minutes to form a uniform ternary precursor sol; c) Template loading: Immerse the biotemplate obtained in step a into the precursor sol obtained in step b, and perform a permeation treatment at a vacuum of -0.09 MPa three times, each time for 15 minutes, to ensure that the precursor sol completely fills the tertiary channels of the biotemplate. d) Gradient calcination: The first stage is nitrogen pre-crystallization, with nitrogen flow rate of 200-250 mL / min, heating to 400-410℃ at 3-4℃ / min, and holding for 2-2.5 hours; the second stage is hydrogen reduction, switching to H2 / Ar mixed gas, heating to 590-630℃ at 5-6℃ / min, and holding for 1-1.2 hours. The third stage involves air stabilization, where the temperature is reduced to 550°C at a rate of 2°C / min in the air atmosphere and held for 3-3.5 hours. e) Post-processing: The calcined product is crushed and stored in a dry nitrogen atmosphere.
3. The preparation method according to claim 2, characterized in that, In step a: Diatomite was selected from fossils of the genus *Clematis*, with a primary pore size distribution of 80-180 nm; the specific surface area of the template before and after hydrofluoric acid treatment increased from 25 m² / m³. 2 / g increased to 210 m 2 / g; After activation with ammonia, the hydroxyl density on the template surface reaches 4.7 OH / nm. 2 .
4. The preparation method according to claim 2, characterized in that, In step b: Four symmetrically distributed waveguide antennas are installed inside the microwave reaction cavity, with a power fluctuation range of ≤±5%; the sol viscosity is controlled at 120-180 mPa·s; and the sol zeta potential is -25 mV to -35 mV.
5. The preparation method according to claim 2, characterized in that, In step d: In the first stage, calcination forms anatase phase nuclei in the material; in the second stage, the hydrogen partial pressure is controlled at 0.05-0.08 MPa, and the activation energy for oxygen vacancy formation is 58 kJ / mol; in the third stage, the relationship between the cooling rate and the stability of oxygen vacancies satisfies: δ = 0.38 - 0.0025 × (cooling rate) 2 .
6. The lithium extraction device based on a biological template-driven ternary doped titanium-based lithium-ion sieve as described in claim 1, characterized in that, include: a) Pretreatment unit: includes pH adjustment unit and temperature control unit; b) Adsorption column unit: a 316 L stainless steel column with a diameter of 300-400 mm and a height of 3600-4800 mm is used, filled with the ternary doped titanium lithium ion sieve as described in claim 1, with a filling height-to-diameter ratio of 10-12:1, and equipped with a distributed temperature sensor. c) Desorption and regeneration unit: including CO2 gas injection unit and hydrochloric acid gradient elution unit; d) Membrane separation unit: spiral wound nanofiltration membrane module, operating pressure 2.5-2.8±0.2 MPa.
7. A lithium extraction process for the lithium extraction apparatus of claim 6, characterized in that: a) Adsorption stage: Lithium ions in the brine are adsorbed using the ternary doped titanium lithium ion sieve described in claim 1, with a feed flow rate of 2.0-2.1 BV / h and a bed pressure drop ≤0.15 MPa / m; b) Desorption stage: CO2 pretreatment time 30±5 minutes, hydrochloric acid elution volume 0.8-1.5 BV; c) Membrane concentration stage: Adjust the pH of the desorption solution, and set the membrane flux to 18-22 L / (m²). 2 •h), lithium ion rejection rate ≥97.5%; d) System lithium recovery rate: ≥92.3%.